Implementing an Interprofessional Education Program in Marriage and Family Therapy: Preparing Students for Interprofessional Practice. - Lal, Arpita; Jonathan, Naveen (American Journal of Family Therapy, 2026)
To address the complex and dynamic needs of today's healthcare industry it is paramount for students to be prepared to work in interprofessional healthcare settings This article describes a collaborative experience at a university where students from the Marriage and Family Therapy (MFT) program engage in an interprofessional education (IPE) experience with students enrolled in other graduate health sciences programs. The benefits and barriers to IPE and interprofessional collaboration (IPC), best practice models of IPE, implications for training mental health practitioners in IPE, and directions for future research, specifically for Couple/Marriage and Family Therapists (C/MFTs) are also addressed.